Consumerism In Mobile Payment - Zul Hilmi, Amalia; Giswandhani, Mariesa (Jurnal Pekommas, 2022)
The purpose of this study was to determine the effect of the convenience of non-cash transactions offered by mobile payment applications on the wasteful behavior of the people of Makassar city. Along with the increasing use of electronic money, this has changed the style of transactions in society. The new media referred to in this study is a mobile payment application. Judging from the development of the transaction model, people tend to choose the practical and easy one. The result of media technology has also contributed to changing the behavior patterns of new media consumption. The payment model has been transformed from cash to non-cash or digital, which the public can easily do. The ease of this transaction led to a change in consumption patterns to meet excessive needs, which led to a wasteful nature. By using a descriptive quantitative approach, researchers distributed questionnaires to 100 research samples. The results of processing the questionnaire data into primary and secondary data in this study are relevant literature studies. The results showed an influence between the ease of transactions using mobile payments and the wasteful behavior of the people of Makassar city.